measuring the quality of philosophical dialogue: a high-inference rating instrument for research and teacher education - bernhard, deborah; helbling, dominik (childhood & philosophy, 2024)
Various studies have shown that philosophizing with children at school can have a positive effect on cognitive, language and social skills. However, previous studies have not considered how the quality of the dialogue influences these outcomes. Addressing this gap, our article introduces a high-inference rating instrument to assess the quality of philosophical dialogue. This instrument features four quality dimensions: Philosophical Richness, Co-construction, Focus, and Restrained Facilitation. It was applied to evaluate 63 class dialogues from a Swiss study involving secondary-school students. The article presents the instrument using excerpts from the study, along with initial validation information, showing its reliability in measuring philosophical dialogue quality. The significance of this research lies in its focus on the quality of philosophical dialogue, an aspect often overlooked in educational settings. By providing a tool to assess this quality, we open up new pathways for analyzing the effectiveness of philosophical dialogues in schools. This is especially relevant as educational systems increasingly recognize the importance of developing students’ critical thinking and discussion skills. The findings highlight the potential of high-quality philosophical dialogues to enrich students’ educational experiences and offer insights for educators and researchers into enhancing these interactions. This study contributes to a deeper understanding of how philosophical dialogue can be used as a powerful educational tool, not just for engaging students but for fostering meaningful and impactful learning.